El emprendimiento como factor clave en el desarrollo económico de la parroquia Santiago provincia Bolívar al año 2019 - Ortega Lema, Luis David (2020)
The present research work is carried out in order to know the impact of the enterprises in the economic development of the Santiago - Prov. Bolívar parish, because nowadays entrepreneurship is fundamental for the local and national growth of a country, to in turn, with the creation of businesses, employment opportunities are offered to the community. From the investigation different aspects were known such as: the motivations to undertake, obstacles that arise at the time of starting the project, factors of business success and also how it has improved the living conditions of the entrepreneurs of the parish. The type of research that will be used is descriptive and field because it allows you to interact directly with the phenomenon of study and identify the characteristics of the ventures as well as the factors that affect social and economic development, qualitative research to know the characteristics present in the business and quantitative to identify the number of ventures generated in the parish. Among the techniques used for the collection of primary information regarding entrepreneurship as well as the socio-economic development of the parish, the respective survey aimed at entrepreneurs and the interview for the government authorities of the community were used, according to the data analysis The factors that affect the creation of the enterprises are also presented, as well as the impact they generate on the social and economic development of the Santiago parish. Keywords: entrepreneurship, entrepreneurship, entrepreneur, business, project, economic development, social development